Partnerships for the Sustainable Development Goals (SDGs) - Murphy, David F.; Stott, Leda (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue of Sustainability on "Partnerships for the Sustainable Development Goals (SDGs)" brings together a collection of articles that explore a diverse range of issues and challenges faced by partnership arrangements that seek to support the achievement of the SDGs and the United Nations 2030 Agenda for Sustainable Development. As well as encompassing a diverse range of collaborative forms and themes, and involving a variety of stakeholders, these collaborative initiatives are all notably shaped by the dynamics of the particular contexts in which they operate. These contexts include individual, organizational, sectoral, spatial, and geographical settings. The impact of the COVID-19 pandemic on partnering for the SDGs is also apparent. The interplay between these elements offers a useful global-local context for further inquiry and reflection on how deeper and more meaningful collaborative relationships might be developed to achieve the SDG targets and beyond.